Studi Pengaruh Variasi Bentuk Wave-Piercing Terhadap Hambatan Pada Kapal Katamaran Untuk Meningkatkan Efisiensi Pemakaian Bahan Bakar - Gilang Andika Putra; Arif Winarno (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
The main variable to increasing the ship's fuel efficiency is the ship's resistance generated by the hull shape. The calculation of ship resistance can be done with software. This study aims to determine the total resistance of the ship and estimate the fuel requirements of the catamaran. The catamaran hull design uses a symmetrical catamaran, the same design as the ship model of Jamaluddin et, al. (2012) in the towing tank test. The model obtained is then calculated for ship resistance and fuel requirements. The method of calculating ship resistance is using the Holtrop method. The results of the analysis of ship resistance are obtained from several variations of the wave-piercing model to get a lower resistance value so that more optimal fuel efficiency is achievable. Based on the analysis and calculations using CFD, from 3 variations of the wave-piercing shape, it shows a 6.1% reduction in resistance on the MV6 model with a variation of fn 0.19-0.65. The MV6 model is obtained the resistance value, the most efficient motor fuel consumption of other wave-piercing types.Roman